Qualitative study legal protection of the implementation of anesthesiologists' duties in delegation of doctor authority: legal protection of anesthesiologists in carrying out professional duties - listyaningrum, Tri Hapsari; Sari, Sri Mayang (Universitas 'Aisyiyah Yogyakarta, 2023)
Anesthesiologists have the main duties in Anesthesia Structuring Care services, including pre-, intra, and post-anesthesia. Kepmenkes Number 251 of 2015 concerning National Guidelines for Anesthesiology and Intensive Therapy Medical Services and Minister of Health Regulation Number 31 of 2013 concerning the Implementation of Anesthesia Nurse Work are legal products that regulate the implementation of anesthesia services.Â The two Permenkes have regulated the authority to carry out anesthesia measures and are the responsibility of Anesthesiologists with their expertise and authority. The legal basis for delegation of authority for medical action is contained in the Law on Health Workers in Article 65 paragraph (1); in carrying out health services, health workers can receive a delegation of medical action from medical personnel. This study aims to determine the legal protection of anesthesiologists in carrying out delegation of authority for professional duties in hospitals. This research is qualitative research with the sociological juridical method and single case design. Purposive sampling with interviews with doctors and anesthesiologists related to the delegation of authority of as many as six people.Â The results of this study, anesthesiologists in carrying out their duties, have been protected by the existence of the hospital by law made by the medical committee with the Standard Operating Procedures and Details of Work Authority of doctors and anesthesiologists in hospitals. Research advice to maintain the proper exercise of the anesthesiologist's authority.